Comparing gene expression in deep infiltrating endometriosis with adenomyosis uteri: evidence for dysregulation of oncogene pathways - Marshall, Anne; Kommoss, Felix; Ortmann, H.; Kirchner, Martina; Jauckus, J.; Sinn, Peter; Strowitzki, Thomas; Germeyer, Ariane (Reproductive biology and endocrinology, 2023)
The pathogenesis of deep infiltrating endometriosis (DIE) is poorly understood. It is considered a benign disease but has histologic features of malignancy, such as local invasion or gene mutations. Moreover, it is not clear whether its invasive potential is comparable to that of adenomyosis uteri (FA), or whether it has a different biological background. Therefore, the aim of this study was to molecularly characterize the gene expression signatures of both diseases in order to gain insight into the common or different underlying pathomechanisms and to provide clues to pathomechanisms of tumor development based on these diseases.
Gesehen am 24.05.2023